Pencapaian Kompetensi Geometri Siswa dengan Pembelajaran Kooperatif Tipe Pair Checks dan Teams Games Tournament - Restiani R; Ayu Wulandari; Suyanto S (Journal of Instructional Mathematics, 2020)
Students also have not been able to formulate interactions between given elements, questions to be solved, and appropriate mathematical concepts to solve the problem. As a result, the achievement of students' geometry competencies is in the gap towards the goals. Therefore, this study aims to determine the differences in the achievement of geometry competence of students on plane geometry subject between cooperative learning type Teams Games Tournament (TGT) and pair checks. This research was conducted on a sample of 72 people, that is 36 students with TGT type cooperative learning and 36 students with pair checks type learning. Samples were selected by cluster random sampling. This research is a quasi-experimental with posttest only nonequivalent control group design. Quantitative data were obtained using test instruments. Research data were analyzed by parametric statistics. Based on data analysis, it was concluded that there were differences in achievement of students' geometry competencies between TGT type cooperative learning and pair checks on plane geometry subject. Model pair checks is an alternative to learning geometry.